A smooth permanent surge process - Andrés González (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
In this paper we introduce the Smooth Permanent Surge [SPS] model. The model is an integrated non lineal moving average process with possibly unit roots in the moving average coefficients. The process nests the Stochastic Permanent Break [STOPBREAK] process by Engle and Smith (1999) and in a limiting case it converges to Threshold Integrated Moving Average [TIMA] models by Gonzalo and Martinez (2003). A test of SPS against STOPBREAK process is presented. Additionally, we introduce a new test for testing SPS process against the random walk. The small sample properties of these tests are investigated by Monte Carlo experiments. An application to the stock markets is presented.
Keywords: C12; C15; C22; C51; C52; 330; Linearity test; Monte Carlo testing; Smooth transitions; Moving Averages Models; Permanent Shock; Transitory Shocks; Monte-Carlo-Methode; Stochastischer Prozess